Comparison of programing ANSYS and COSMOS/M finite element systems - Szabó, Ferenc János (Design of machines and structures, 2024)
A simple optimization task is programmed by using the built- in programming possibilities of two finite element systems: ANSYS APDL (Parametric Design Language) and COSMOS/M built-in macro language. The same program is written in the two different programming language and the resulting program listings is compared. The demon-stration optimization problem is to find the minimum safe radius of an L-shape model, loaded by a uniform surface pressure. The program to solve this optimization task builds the model, solves the finite element problem, and iteratively improves the radius until the optimum solution. In both cases, when the program running ends, we will see the optimum structure on the screen, and we can use the menu possibilities of the finite element system to see any details of the optimized model or listing the values of the parameters.